Targeting cardiac natriuretic peptides in the therapy of diabetes and obesity. (1st December 2016) - Moro, Cedric
ABSTRACT: Introduction : Atrial and B-type Natriuretic Peptides (NP) are cardiac hormones with potent cardiovascular and metabolic effects. They signal through the NPRA/cGMP system and are inactivated by a clearance receptor NPRC and neutral endopeptidases (NEP). Recombinant ANP and BNP are currently used as drug treatment for acute decompensated congestive heart failure. Recent literature indicate that a defective NP system is linked to obesity and predict the risk of type 2 diabetes (T2D). Areas covered : This article reviews recent epidemiological, clinical and preclinical evidences that NP system deficiency may be causal of obesity and T2D. The molecular mechanisms of the NP pathway in several metabolic target tissues are presented. The therapeutic potential of NP in obesity and T2D is discussed. Expert opinion : Targeting the NP pathway may offer a novel therapeutic avenue for the management of obesity and T2D. The benefit/risk of drugs increasing circulating NP levels by blocking NPRC and NEP, and/or enhancing NPRA signaling should be assessed in obese and type 2 diabetic individuals.